Classification of Ammonia in water for Oil and Gas Industry using Case Based Reasoning (CBR) - Muhamad Faruqi, Zahari; M. S., Najib; Kamarul Hawari, Ghazali; Fathimah, Abdul Halim; Abdul Aziz, Mohd Azoddein (Penerbit UMP, 2016)
Toxic gasses are exists in environment such as benzene, ammonia and others. Ammonia highly dissolves in water which is sources of human and other species. If the ammonia have high concentration, the effect of human health will be dangerous. Then, using proper monitoring and wastewater management the hazard can be prevented. This paper proposed the intelligence classification technique using an Electronic Nose (E-nose) measurement.The sensor array in the E - nose are used for the inputs of the Case Based Reasoning (CBR) for intelligent classification. The experimental result shows that the technique accomplished to classify with high accuracy which is 100% of accuracy.